The negative impacts of human activities on the ecological corridor in the karst highly urbanized area are gradually diminishing: A case study from the karst mountain cities in Southwest China - Qi Yuan; Rui Li (Ecological Indicators, 2023)
Karst mountain cities are important population agglomerations in southwestern China, as well as integral components of the significant regional economic belt - the Central Guizhou Economic Belt. Ecological corridors serve as crucial pathways for species migration and play a vital role in integrating regional habitats, particularly in the highly fragmented and ecologically vulnerable karst areas. However, it is not yet clear how human activities and natural factors drive the distribution of ecological corridors in the rapidly expanding urban areas of karst region. In light of this, based on multi-source data from 2005 to 2020, this study identified ecological source areas using ecological sensitivity analysis and a resistance surface model was adjusted using the rocky desertification factor. The Minimum Cumulative Resistance (MCR) model was employed to extract ecological corridors for each of the four time periods. Furthermore, space syntax analysis was conducted to evaluate the selection, integration, and depth of the corridors under different levels of urbanization. Finally, correlation analysis in R language was performed to determine the degree of influence of various driving factors on the distribution of ecological corridors. Our findings indicate that during the urbanization process, the negative impact of human disturbance factors on corridor distribution in highly urbanized areas has decreased. And the overall development of ecological corridors in the research region has shown improvement over the past 20 years. However, extreme climatic conditions have negatively affected the distribution of ecological corridors. Additionally, policy-driven measures will have an impact on the distribution of ecological corridors. By exploring the spatiotemporal differentiation and driving mechanisms of corridors in Karst mountain cities over the past two decades, our research will provide scientific evidence for biodiversity conservation and the construction of ecologically secure environments in karst areas.